Inflation Rate, Money Supply, IHSG - Hadi, Nico (IAIN Kendari, 2023)
AbstractThe global economy faces various challenges and difficulties, with factors such as the spread of the COVID-19 virus and the ongoing conflict between Russia and Ukraine exacerbating the world's economic conditions. This has led to a global economic crisis, including food shortages, energy constraints, and worldwide inflation. Given these circumstances, this research utilizes the Composite Stock Price Index (IHSG) as the dependent variable, with inflation rate, money supply, and central bank exchange rates (BI Rate) as independent variables. The study is conducted quantitatively, using secondary data collected from websites and analyzed using SPSS 25 and Eviews 12 (64). The research findings indicate that inflation does not significantly impact IHSG, suggesting that companies may experience adverse effects when inflation rises, leading investors to liquidate their assets and seek alternative forms of investment. Additionally, the BI Rate does not have a significant influence on IHSG, while the money supply has a significant impact on IHSG. AbstrakPerekonomian di dunia sekarang sedang mengalami berbagai macam tantangan dan kesulitan. Salah satunya disebabkan oleh penyebaran virus Covid-19 dan juga peperangan yang terjadi antara Rusia dan Ukraina, dimana turut memperburuk kondisi perekonomian dunia yang menyebabkan krisis pangan, keterbatasan energi, dan inflasi dunia. sehingga penelitian ini dilakukan menggunakan indeks harga saham gabungan (IHSG) sebagai variabel dependen dan tingkat inflasi, jumlah uang beredar dan kurs BI sebagai variabel independen. Penelitian yang dilakukan bersifat kuantitatif dengan data sekunder yang di dapatkan dari website. Penelitian ini juga diolah menggunakan aplikasi Spss 25 dan Eviews 12 (64). Hasil penelitian menunjukan bahwa variabel inflasi tidak berpengaruh signifikan terhadap IHSG. Dengan hasil ini menunjukan bahwa perusahaan akan memeperoleh dampak buruk Ketika inflasi meningkat yang membuat investor akan segera mencairkan dananya dan menginvestasikannya ke bentuk investasilain. Dan juga BI Rate tidak berpengaruh signifikan terhadap IHSG. Sedangkan jumlah uang beredar berpengaruh signifikan terhadap IHSG.